A perspective on the future possibilities for research by health care professionals - Susanne Perkhofer; Heidi Oberhauser (Forum Neue Medien in der Lehre Austria, 2012)
Midwives, members of allied health professionals and nurses make up 64 % of the personnel in the Austrian health sector. These occupational groups are now being educated at the tertiary level - at universities of applied sciences. Due to this academisation, health professionals have to meet the challenge of conducting research on their own or in collaboration with others. While some European countries are already experienced in doing research, Austria is just beginning to do so. This article focuses on the demands placed upon universities of applied sciences and collaborations that could potentially strenghten their research capabilities. It also highlights the critical aspects of conducting research within these young academic disciplines and describes research strategies for performing this research. 30.03.2012 | Susanne Perkhofer & Heidi Oberhauser (Innsbruck)